The Use of Modern Pedagogical Technologies in Teaching Information Security - Jasur Isroilovich Boymanov (Researchparks Publishing, 2026)
This work provides an in-depth analysis of the methods for forming fundamental knowledge in the process of teaching information security technologies. In the modern digital society, ensuring the security of information resources and information systems has become one of the most important socio-economic and technological challenges. Therefore, training specialists in the field of information security who possess qualified, profound theoretical knowledge and can adapt to rapidly changing technological environments is one of the pressing issues in the education system. The paper elucidates the concept of educational fundamentalization and its close connection with teaching information security disciplines. Fundamental knowledge includes not only practical skills but also a deep understanding of basic concepts such as cryptography principles, mathematical and logical protection of information, algorithm theory, network technologies, operating system architecture, and security policies. The article systematizes and defines effective approaches to forming fundamental knowledge, which is necessary for successfully teaching information security technologies. This includes, in particular, focusing on interdisciplinary integration of study objectives; problem-based learning and teaching conceptual modeling; alignment of theory with practical application; and a focus on the development of analytical and logical thought. This way they do not only use a tool, but understand the theoretical basis for security processes.